Sistem Informasi Inventory Obat Pada UKM KSR ITB STIKOM Bali Berbasis Website - Devi, Ni Luh Putu Satya; Hadi, Rosalia; Saputra, I Made Arya Budhi (STMIK Banjarbaru, 2024)
UKM KSR ITB STIKOM Bali is a student activity unit that provides health services to the ITB STIKOM Bali campus community. The KSR UKM ITB STIKOM Bali requires effective drug inventory management. The problem is that drug recording is still manual, causing inefficiency and difficulty in monitoring. Therefore, a website-based Drug Inventory System was developed using the Laravel framework. This framework structures the source code and facilitates development. The aim of this application is to improve efficiency, accuracy, and transparency in drug inventory management. The research method used in this study is the waterfall method, which is an integral part of the SDLC (System Development Life Cycle), showing its characteristic features in each stage of implementation. The model design uses DFD, and the database employs ERD, conceptual database, and table structure. The system was tested using blackbox testing and evaluated by 30 respondents through a questionnaire, yielding a score of 85.93%, indicating a